Soft Rush (Juncus effusus) Biology and Control in Pastures - Brent Sellers; Jason Ferrell; Reyna Speckmann (EDIS)
SS-AGR-325, a 3-page illustrated fact sheet by Brent Sellers, Jason Ferrell, and Reyna Speckmann, describes this clump-forming perennial plant that frequently infests low-lying areas in Florida pastures — biology, control, forage tolerance, management, and recommendations. Published by the UF Department of Agronomy, November 2009.